2011
DOI: 10.1891/0730-0832.30.5.291
|View full text |Cite
|
Sign up to set email alerts
|

Wound Care in the Neonatal Intensive Care Unit

Abstract: The skin is a vital organ with key protective functions. Infants in the NICU are at risk for skin injury because of developmental immaturity and intensive care treatments. When skin injury occurs, the neonatal nurse is challenged to provide wound care to optimize functional and cosmetic healing. Optimal wound care requires basic knowledge of the mechanisms of injury, physiology of wound healing, host factors affecting wound healing, and wound assessment. This knowledge provides the basis for determining approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 19 publications
0
59
0
21
Order By: Relevance
“…The choice of the product depends on the type of tissue that lies on the bed of the lesion, the depth of the lesion, the amount of exudates, and the presence of signs of local infection (5) . It is necessary to select a product that provides an adequate environment for healing by maintaining adequate moisture.…”
Section: Doubts About What Can Be Used In Newborn Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of the product depends on the type of tissue that lies on the bed of the lesion, the depth of the lesion, the amount of exudates, and the presence of signs of local infection (5) . It is necessary to select a product that provides an adequate environment for healing by maintaining adequate moisture.…”
Section: Doubts About What Can Be Used In Newborn Childrenmentioning
confidence: 99%
“…Only one study was found (5) regarding the effectiveness of the use of this product in newborn children and there is no evidence to ensure the absence of longterm risks in using this type of dressing.…”
Section: Doubts About What Can Be Used In Newborn Childrenmentioning
confidence: 99%
See 3 more Smart Citations